2024
DOI: 10.1101/2024.02.09.24302276
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sub-second and multi-second dopamine dynamics underlie variability in human time perception

Renata Sadibolova,
Emily K. DiMarco,
Angela Jiang
et al.

Abstract: Timing behaviour and the perception of time are fundamental to cognitive and emotional processes in humans. In non-human model organisms, the neuromodulator dopamine has been associated with variations in timing behaviour, but the connection between variations in dopamine levels and the human experience of time has not been directly assessed. Here, we report how dopamine levels in human striatum, measured with sub-second temporal resolution during awake deep brain stimulation surgery, relate to participants pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
(180 reference statements)
0
1
0
Order By: Relevance
“…Wiener and colleagues identified an association between dopaminergic system genes and timing in humans (Wiener, et al, 2011). More recently, it has been demonstrated that rapid changes in dopamine neuron activity in mice (Jakob et al, 2022), manipulation of dopamine neuron activity using optogenetic methods in mice (Soares et al, 2016), and rapid (i.e., sub-second) and slow (i.e., several seconds) changes in dopamine levels in humans affects timing behavior and time perception (Sadibolova, et al, 2024; Sadibolova, et al, 2022; Terhune, et al, 2016). Notably, many of the methods used to implicate, measure, or manipulate dopamine levels during instrumental timing behavior is also used to investigate dopamine’s role in instrumental (and Pavlovian) reinforcement and learning (Frank & Fossella, 2011; Kishida & Sands, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Wiener and colleagues identified an association between dopaminergic system genes and timing in humans (Wiener, et al, 2011). More recently, it has been demonstrated that rapid changes in dopamine neuron activity in mice (Jakob et al, 2022), manipulation of dopamine neuron activity using optogenetic methods in mice (Soares et al, 2016), and rapid (i.e., sub-second) and slow (i.e., several seconds) changes in dopamine levels in humans affects timing behavior and time perception (Sadibolova, et al, 2024; Sadibolova, et al, 2022; Terhune, et al, 2016). Notably, many of the methods used to implicate, measure, or manipulate dopamine levels during instrumental timing behavior is also used to investigate dopamine’s role in instrumental (and Pavlovian) reinforcement and learning (Frank & Fossella, 2011; Kishida & Sands, 2021).…”
Section: Introductionmentioning
confidence: 99%